A systematic review on the definition, criteria, indicators, methods and applications behind the Ecological Value term - F. Amador-Cruz (Elsevier, 2021)
The “Ecological Value” (EV) term has been spread in the literature since 1860; however, there is no consensus on its definition and the criteria for its assessment. To identify, assess and summarize the main definitions, criteria, indicators and applications behind the EV term, we performed a systematic literature review of 209 articles published over the last 10 years. Methods included documentation of the following data: i) study area, ii) study subject, iii) study object; iv) criteria, indicators and methods used in the analyses, v) applications of the EV term, and vi) if the study was performed in a natural protected area. Multiple Correspondence Analysis (MCA) was conducted to uncover the association among studies regarding the use of EV and to test for homogeneity among the articles publishing research involving EV. A bootstrap technique was used for MCA validation. The main findings exposed the polysemy of the term and the paucity in the definition, mainly derived by the lack of a theoretical framework. Only 74, out of the 209 revised articles, involved numerical analysis to evaluate criteria. The more recurrent criteria were those related with ecological properties (biodiversity, vulnerability) and with functional characteristics (fragmentation, connectivity and resilience). Remote sensing techniques were the more frequent method for the assessment of EV. The main applications in the use of this term were for natural and urban planning, biodiversity conservation and payment for ecosystem services. An explicit heterogeneity among articles, with and without numerical analysis, was denoted by MCA. Finally, we concluded that the EV term is highly related with the intrinsic values of the landscape.